1992
DOI: 10.1099/00221287-138-12-2673
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyst envelope thickness, heterocyst frequency and nitrogenase activity in Anabaena flos-aquae: influence of exogenous oxygen tension

Abstract: The heterocyst envelope of the N,-fixing cyanobacterium Anabaenaflos-aquae thickened as exogenous 0, partial pressure (PO,) was increased from 5 to 40 kPa. The majority of the thickening occurred in the glycolipid layer area of the envelope. Such thickening appears to be an 0,-induced mechanism for providing a greater 0, diffusion barrier against 0, inhibition of nitrogenase. Nitrogenase activity decreased at PO, levels above ambient (20 kPa), indicating that a thicker envelope is not completely effective as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Importantly, this speculative link between the isotopic effect and heterocyst number is merely a hypothesis suggested by our observed data and should be further investigated. Previous studies have shown that heterocyst frequency does not directly correlate with nitrogenase activity (e.g., Kangatharalingam, Priscu, & Paerl, 1992), and we acknowledge this relationship is likely more complex than our interpretation. However, given that pN 2 exerts a clear influence on heterocyst frequency (Figure 4), we interrogate our data under the assumption that (with all other parameters equal) pN 2 affects the kinetics of nitrogenase.…”
Section: Nitrogen Isotope Fractionation In Anabaena Speciesmentioning
confidence: 49%
“…Importantly, this speculative link between the isotopic effect and heterocyst number is merely a hypothesis suggested by our observed data and should be further investigated. Previous studies have shown that heterocyst frequency does not directly correlate with nitrogenase activity (e.g., Kangatharalingam, Priscu, & Paerl, 1992), and we acknowledge this relationship is likely more complex than our interpretation. However, given that pN 2 exerts a clear influence on heterocyst frequency (Figure 4), we interrogate our data under the assumption that (with all other parameters equal) pN 2 affects the kinetics of nitrogenase.…”
Section: Nitrogen Isotope Fractionation In Anabaena Speciesmentioning
confidence: 49%
“…An apparent increase in the average thickness of the glycolipid layer in DR1822 relative to that in the wild-type strain (Fig. 4) may be a response to penetration of oxygen (23).…”
Section: Resultsmentioning
confidence: 99%
“…Under the controlled conditions in which isolated strains are grown, the need for different HG types may not be as high as in natural environments, thus resulting in more simple HG profiles. In this sense, Kangatharalingam et al (1992), for example, demonstrated that heterocyst glycolipid-layer thickness was dependent on exogenous oxygen tension. Whether such thickening could imply changes in the HG composition remains unknown.…”
Section: Environmental Factors Influencing Hg Distribution-mentioning
confidence: 99%